Development of nanocomposite nanowires by electrospinning as a supercapacitor electrode with high energy density, power density and rate capability - Vidyadharan , Baiju (2015)
Deployment of renewable energy requires, in addition to efficient energy conversion devices, electrochemical materials capable of storing a large amount of electrical energy as well as delivering it at a high rate. Electrochemical capacitors represent a class of energy storage devices; thus optimizing the working electrodes for them is the key to achieving high energy (ES) and power densities (PS). However, ES and PS are not united in the existing devices. High electrochemical reversibility, multiple oxidation states, high surface area and high electrical conductivity are requirements for high ES and PS in supercapacitor electrodes. Most materials offering high theoretical capacitance owing to its multiple oxidation states have lesser electrical conductivity; therefore, it is hypothesized that the electrical conductivity plays a dominant role in combining ES and PS in a single device. One-dimensional (1D) nanowires show improved charge transport properties compared to their nanoparticle analogue; therefore, they are expected to deliver simultaneously ES and PS in a single device. Studies show that the ceramic electrode materials exhibits diverse range of capacitances and conductivities than other choice of materials; therefore, the target device could be achieved using ceramic electrodes. Three typical materials with nanowire morphology are chosen for this purpose, viz. copper oxide (CuO), nickel oxide (NiO), and cobalt oxide (Co3O4). Among them NiO and Co3O4 show larger theoretical capacitance estimated at 2570 and 3560 Fg-1 respectively, compared to CuO (1800 Fg-1); the later has larger electrical conductivity. Synthesizing a composite is one of the methods to combine the functions of different materials; therefore, CuO+NiO and CuO+Co3O4 composites are the target materials. These materials were synthesized as 1D nanowires using an aqueous polymeric solution based electrospinning process and their structural properties by X-ray and electron diffraction were studied, high resolution transmission electron microscopy; morphological properties by scanning and transmission electron microscopy; and electrochemical properties by cyclic voltammetry, galvanostatic charge discharge cycling, and electrochemical impedance spectroscopy. The electrochemical studies showed that CuO, NiO and Co3O4 achieve a specific capacitance (CS) nearly 30% of its theoretical value, but with low rate capability. The studies showed higher rate capability, lower equivalent series and charge transfer resistances in NiO + CuO and Co3O4+CuO composites than those of their single components. Asymmetric supercapacitor (ASC) using ceramic nanowire anode and commercially available activated carbon cathode were fabricated and their charge storage performance was compared with a symmetric supercapacitor fabricated using activated carbon at both electrodes. The ASC showed seven times higher specific capacitance and ES compared to the symmetric device. The PS decreased with ES for devices employed single component ceramic nanowires. However, ES remained practically same for increased PS when their composite mixture was used as working electrode. An ES of ~52.6 Whkg-1 with PS of ~14000 Wkg-1 is delivered by Co3O4+CuO based device which appear to be the best ever achieved in supercapacitor charge storage mode